Vocal and motor behaviors as a possible expression of gastrointestinal problems in preschoolers with Autism Spectrum Disorder - Margherita Prosperi; Elisa Santocchi; Filippo Muratori; Chiara Narducci; Sara Calderoni; Raffaella Tancredi; Maria Aurora Morales; Letizia Guiducci (BMC, 2019)
Abstract Background Gastrointestinal (GI) problems are one of the most frequent comorbidities in Autism Spectrum Disorder (ASD) but can be under-recognized due to the concomitant communication difficulties of this population. Accordingly, some associated behaviors (AB) such as verbal and motor behaviors (VB and MB, respectively) have been identified as a possible expression of an underlying GI problem and evaluated through an ad hoc questionnaire (the Associated Behaviors Questionnaire -ABQ-). The aims of this study were to investigate the presence and the type of AB in an Italian sample of ASD preschoolers, and to determine their correlations with GI problems. Methods We included 85 ASD preschoolers (mean age 4.14 years; SD 1.08) splitted into two groups (GI and No-GI) through the GI Severity Index instrument. AB were evaluated through the ABQ that includes VB, MB and Changes in overall state (C) clusters. Specific tools were administered to evaluate the ASD core ad associated symptoms, as well as the intellective and adaptive functioning. Results The GI group (N = 30) showed significantly higher scores in all the three ABQ areas (VB, MB and C) than the No-GI group (N = 55), with a positive correlation between GI symptoms and some specific AB as well as ABQ Total score. By dividing the whole sample in verbal and non-verbal individuals, both specific and shared AB emerged in the two groups. Conclusions Our results alert clinicians to consider behavioral manifestations as a possible expression of GI problems in ASD subjects. Therefore, the evaluation of AB may be useful to identify the presence of GI problems in the ASD populations, and especially in non-verbal ASD children.